Tissue-Specific Transcriptomes in the Secondary Cell Wall Provide an Understanding of Stem Growth Enhancement in Solidago canadensis during Invasion - Yu Zhang; Zhongsai Tian; Jiaqi Shi; Ruoyu Yu; Shuxin Zhang; Sheng Qiang (Biology, 2023)
Invasive plants generally present a significant enhancement in aboveground vegetative growth, which is mainly caused by variation in secondary cell wall (SCW) deposition and vascular tissue development. However, the coordination of the transcriptional regulators of SCW biosynthesis is complex, and a comprehensive regulation map has not yet been clarified at a transcriptional level to explain the invasive mechanism of S. canadensis. Here, RNA sequencing was performed in the phloem and xylem of two typical native (US01) and invasive (CN25) S. canadensis populations with different stem morphologies. A total of 296.14 million high-quality clean reads were generated; 438,605 transcripts and 156,968 unigenes were assembled; and 66,648 and 19,510 differential expression genes (DEGs) were identified in the phloem and xylem, respectively. Bioinformatics analysis indicated that the SCW transcriptional network was dramatically altered during the successful invasion of S.canadensis. Based on a comprehensive analysis of SCW deposition gene expression profiles, we revealed that the invasive population is dedicated to synthesizing cellulose and reducing lignification, leading to an SCW with high cellulose content and low lignin content. A hypothesis thus has been proposed to explain the enhanced stem growth of S. canadensis through the modification of the SCW composition.